Nursing workforce competencies and job satisfaction: the role of technology integration, self-efficacy, social support, and prior experience - Mohammed Hamdan Alshammari; Atallah Alenezi (BMC, 2023)
Abstract Background The nursing profession has significant importance in delivering high-quality healthcare services. Nursing practitioners who have essential competencies and who are satisfied with their job are vital in achieving optimum patient outcomes. Understanding the effects of technology integration on nurse workforce competencies and job satisfaction is crucial due to the fast progress of technology in healthcare settings. Furthermore, many elements, including self-efficacy, social support, and prior experience have been recognized as possible mediators or moderators within this association. The primary objective of this quantitative research was to examine the influence of nursing education and the integration of technology on the competencies and job satisfaction of nursing professionals. Additionally, this study aimed to explore the potential mediating and moderating effects of self-efficacy and social support in this relationship. Methods This cross-sectional, quantitative study employed an online survey questionnaire with standardized scales to measure nursing workforce competencies, job satisfaction, self-efficacy, social support, and prior experience. It was completed by 210 registered nurses from various healthcare settings in the Kingdom of Saudi Arabia. Data were analyzed by descriptive statistics, Pearson correlation analysis, multiple regression analysis, and structural equation modeling performed with SPSS 23 and SmartPLS 3.0 software. Results The study's findings revealed that nursing workforce competencies and job satisfaction were significantly predicted by nursing training and technology integration. The relationship between nursing training and technology integration, as well as nursing workforce competencies and job satisfaction, was partially mediated by self-efficacy and social support. Furthermore, prior experience moderated the relationship between nursing education and technological integration, nursing workforce competencies, and job satisfaction. Conclusions The study's findings suggest that nursing training and technology integration can improve nursing workforce competencies and job satisfaction and that self-efficacy and social support play an important role in mediating this relationship. Furthermore, prior experience can have an impact on the efficacy of nursing training and technology integration programs for developing nursing workforce competencies. The study has several practical implications for nursing education, training, and professional development programs, as well as strategies used by healthcare organizations to improve nursing workforce competencies and job satisfaction. To maximize their impact on nursing workforce competencies and job satisfaction, this study recommends that nursing training and technology integration programs focus on enhancing self-efficacy and social support. Furthermore, the study emphasizes the significance of prior experience when designing and implementing nursing training and technology integration programs.